Regionalisme Hadis di Minangkabau: Pengaruh Konteks Sosio-Historis Terhadap Kitab Hadis Hidayatu al-Thalibin Karya Buya Manshur - Chalida, Sri; Gusnanda, Gusnanda; Pinto, Nandi; Irwansyah, Ade; Afriadi, Afriadi; Gusnanda (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2024)
This article examines the ideological struggle that influenced the creation of the hadith book Hidayatu al-Thalibin by Buya Manshur, within the intellectual tradition of Minangkabau. This manuscript is crucial for understanding the transmission of hadith in the social, cultural, and political context of early 20th century Minangkabau. The era's colonialism and Islamic renewal movements impacted not only economic and political spheres but also intellectual dynamics, including hadith discourse. A qualitative approach, incorporating both textual and non-textual analysis, was employed to understand the socio-historical context influencing the book's writing process. Data were gathered through documentation and analysis of relevant texts and historical records. The study found that the religious struggle between traditionalists (kaum tuo) and modernists (kaum mudo) in the early 20th century significantly shaped the intellectual narrative of Hidayatu al-Thalibin. The book served as a medium for reinforcing the ideological identity of the traditionalists while also reflecting social criticism and cultural strategies in response to changes in Minangkabau. These findings highlight the importance of studying hadith regionalism to understand the social, cultural, and political dynamics influencing the development of local Islamic traditions, particularly in the Nusantara context. The implications underscore the need for further research into how regional socio-historical contexts shape religious texts and discourses.